IMPLEMENTASI UNIFIED APPROACH METHODE PADA TRANSAKSI PENYEWAAN FREEZER CV.BDR PADANG - Ahmad Kamal; Renita Astri (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2019)
The author has conducted research at CV.BDR in order to know and departure information systemrental fleet in progress and further develop a system that is running in order to achieve a more optimallevel. In this study the author uses Visual Basic 6.0 programming language for programming. Fromthe data collected, then the writer uses the method of processing the results of laboratory research data computers. From the results of this study designed a rental application and departure of ships that can help job employees, where the data is done in the design of the development of the information generated from the old system and there is a way of working of the system itself by means of computeruse as a tool and replace the software that used in data processing. It is hoped that the authorsdesigned a new system could replace the old system in the form of a manual system, in order to achieve the level of effectiveness and higher efficiency. So that the design could be beneficial to CV.BDR inthe data processing to obtain rental information and a more accurate vessel departure and may assistin decision making.